(untitled) (PJDOL, 2023)
The paper presents the findings of a study conducted to develop open and distance learning model for revival of education system in disaster struck areas. A random and stratified sample of students of 51 colleges of Azad Jammu and Kashmir and Khyber Pakhtunkhwa has been taken. All available Education faculty members from Allama Iqbal Open University and Senior Management Staff of Earthquake Reconstruction Rehabilitation Authority have been taken as a sample